2017
DOI: 10.1089/ars.2017.7121
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Glutathione: Regulation and Functions

Abstract: We postulate that the application of genetically encoded sensors for glutathione in combination with novel HO probes and conventional biochemical redox state assays will lead to fundamental new insights into mitochondrial redox regulation and reinvigorate research into the physiological relevance of mitochondrial redox changes. Antioxid. Redox Signal. 27, 1162-1177.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 137 publications
3
88
0
1
Order By: Relevance
“…The GSH/ GSSG ratio in the cytosol is typically ‡30:1-100:1 with a redox potential of -290 mV; this ratio in the mitochondria is estimated to be >100:1 with a redox potential of £ -300 mV. By contrast, this ratio appears to be 1:1 to 3:1 in the ER with a redox potential of -175 to -185 mV, which accounts for the relatively oxidizing environment of the ER (9,25,75,88).…”
Section: Cellular Distribution Of the Gsh/gssg Couplementioning
confidence: 95%
See 1 more Smart Citation
“…The GSH/ GSSG ratio in the cytosol is typically ‡30:1-100:1 with a redox potential of -290 mV; this ratio in the mitochondria is estimated to be >100:1 with a redox potential of £ -300 mV. By contrast, this ratio appears to be 1:1 to 3:1 in the ER with a redox potential of -175 to -185 mV, which accounts for the relatively oxidizing environment of the ER (9,25,75,88).…”
Section: Cellular Distribution Of the Gsh/gssg Couplementioning
confidence: 95%
“…5). The a-KG carrier (encoded by SLC25A11) and the dicarboxylate transport mechanisms (dicarboxylate carrier, encoded by SLC25A10) are two potential candidates for importing cytosolic GSH to the mitochondria, mainly in the kidney and liver; the tricarboxylate carrier (encoded by SLC25A1) is a potential GSH transporter in the brain and astrocytes (9,79). By contrast, some organelles, such as the nucleus, have their own GSH pools, which are independent of cytosolic GSH (88).…”
Section: Cellular Distribution Of the Gsh/gssg Couplementioning
confidence: 99%
“…Experiments with rxYFP and roGFP-based sensors indicate that the matrix glutathione pool is highly reduced, E GSH < −300 mV, similar to the cytosol (Calabrese et al 2017;Hanson et al 2004;Hu et al 2008;Kojer et al 2012;Morgan et al 2011). However, irrespective of the identity of the glutathione transporters in the IMM, it appears that the transport of glutathione across the IMM is very slow.…”
Section: The Matrix Glutathione Pool Appears To Be Kinetically Isolatmentioning
confidence: 99%
“…It is well known that intracellular GSH works as a free radical scavenger, which protects cells against ROS, and that the accumulation of proteins with irreversible thiol oxidation is a parameter of ROS-induced cellular damage (Kettenhofen & Wood, 2010). It was reported that the mitochondrial sulfhydryl group was also a critical target site for chemical compounds in rat hepatocytes (Calabrese, Morgan, & Riemer, 2017;Chernyak & Bernardi, 1996;Nakagawa et al, 2014). Previous studies showed that the oxidation of GSH to GSSG caused the formation of mixed disulfides between GSSG and cellular protein thiols and that a factor in their formation is related to the concentration of intracellular GSSG (Fawthrop, Boobis, & Davies, 1991;Nakagawa, Moldéus, & Cotgreave, 1992;Reed, 1990), suggesting that a slight loss of protein thiols caused by DETX may be dependent on the formation of mixed disulfides ( Figure 4).…”
Section: Comparative Cytotoxic Effects Of Xanthone and Thioxanthonementioning
confidence: 99%
“…Previous studies showed that the oxidation of GSH to GSSG caused the formation of mixed disulfides between GSSG and cellular protein thiols and that a factor in their formation is related to the concentration of intracellular GSSG (Fawthrop, Boobis, & Davies, 1991;Nakagawa, Moldéus, & Cotgreave, 1992;Reed, 1990), suggesting that a slight loss of protein thiols caused by DETX may be dependent on the formation of mixed disulfides ( Figure 4). It was reported that the mitochondrial sulfhydryl group was also a critical target site for chemical compounds in rat hepatocytes (Calabrese, Morgan, & Riemer, 2017;Chernyak & Bernardi, 1996;Nakagawa et al, 2014).…”
Section: Comparative Cytotoxic Effects Of Xanthone and Thioxanthonementioning
confidence: 99%